2017
DOI: 10.1039/c6nr09408b
|View full text |Cite
|
Sign up to set email alerts
|

Defining the copper binding aptamotif and aptamer integrated recovery platform (AIRP)

Abstract: The potential copper binding sites in aptamers have been predicted on the basis of secondary structures and the binding affinity of aptamers with copper. Out of the 4 aptamers (Cu-A1 to Cu-A4) selected by SELEX and examined in the present study, the Cu-A2 aptamer shows the highest binding affinity to copper with the lowest K value of 1.83 × 10 M. In order to confirm the binding of copper to the proposed region, the binding affinity was experimentally validated using mutation and deletion analysis. We have conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…This implies that the cell specific aptamers were saturated and enriched during the SELEX processes. To further demonstrate the difference in binding ability round by round, we employed real-time PCR (RT-PCR), which proved valuable in validating the optimal state of DNA aptamer enrichment [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the cell specific aptamers were saturated and enriched during the SELEX processes. To further demonstrate the difference in binding ability round by round, we employed real-time PCR (RT-PCR), which proved valuable in validating the optimal state of DNA aptamer enrichment [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…An aptamer is an artificial single-stranded oligonucleotide that can be specifically isolated through the Systematic Evolution of Ligands by exponential enrichment (SELEX) process and capable of recognizing a variety of targets in systemically designed detection platforms [ 17 , 18 , 19 , 20 ]. Some studies have reported ingenious efforts to combine the recognition ability of aptamers with advanced nanomaterials in the field of drug delivery and targeted therapeutics because of their strong stability under a wide range of temperature, pH and in-vivo/ex-vivo conditions [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“… 20 23 Today, there are some chemiluminescence immunoassay (CLIA)-compliant diagnostic tests based on ASPH detection utilizing enzyme-linked immunosorbent assay (ELISA) to diagnose or monitor a series of cancers. 24 ASPH is also known as the target of immunohistochemical staining in some tumors including hepatocellular carcinoma, cholangiocarcinomas, and lung carcinoma. 21 , 25 28 Moreover, ASPH has recently attracted more attention as a potent target for tumor therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, easy chemical modifications, such as 5′ amine modification and Cy5-labeling, as well as the stability of aptamers, make them attractive agents [ 18 ]. Due to these advantages, aptamers are used in various fields, including imaging, drug delivery, and as biosensors [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%